Analisis Pengelolaan Tanah Wakaf dalam Menciptakan Kesejahteraan Masyarakat: Studi Kasus Kecamatan Mandiangin - Rina Pradita Ariyani; A. Tarmizi; Ahmad Syahrizal (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research is entitled Analysis of Waqf Land Management in Creating Community Welfare (Case Study of Mandiangin District). The research method used by researchers is a qualitative approach. The results of this research are: 1) The management of waqf land in Suka Maju Village includes: the waqf land manager receives waqf land from the community in Suka Maju Village, then the waqf land manager manages the waqf land, after that allocates the results of managing the waqf land to various community needs in Suka Maju Village. Meanwhile, the waqf land in Suka Maju Village itself comes from the community in Suka Maju Village. After the acceptance stage of the waqf land has been accommodated, the next stage is the stage of managing and allocating the waqf land which is distributed to the Suka Maju Village Government with the general aim of religious and public interests. There are 6 waqf lands in Suka Maju Village until 2023 which come from the Suka Maju Village community with different land sizes. Meanwhile, the use of waqf land in Suka Maju Village is used in 2 sectors, namely 1) Education sector. The waqf land collected in Suka Maju Village is used for the education sector with an area of 600m2, namely for the construction of elementary schools and PAUD. 2) Religious sector, waqf land collected in Suka Maju Village, is used for the religious sector with an area of 1200m2, namely for the construction of mosques and prayer rooms. 2) The impact of wakah land management in creating welfare for the people of Suka Maju Village can be seen from 4 indicators of community welfare, namely income, health, education and religion. In the dimension of health or care for the soul in an Islamic perspective, the role of waqf land in Suka Maju Village has not succeeded in realizing care for the soul as measured by the community's ability to easily get access to health cards, health access services and the ability to provide treatment if a family member is sick. In terms of the development of the educational dimension or maintenance of reason in the management of waqf land, the impact of waqf land in Suka Maju Village has been to be able to meet the educational needs of the village community in the form of sending children in Suka Maju Village to school at the formal education level. In the development of the income or asset maintenance dimension in asset allocation, the existence of waqf land in Suka Maju Village has not been able to provide an impact or contribution to the income of the community or the village government. From a religious perspective, the existence of a religious institution that stands on waqf land in Suka Maju Village has had a positive impact in improving community welfare in the religious sector in the form of increasing piety. Therefore, the Suka Maju Village Government has carried out the role of waqf land in the form of religious protection or hifdz a-din, namely creating prosperity from a religious perspective.